Heating body and preparation method thereof
By applying an external magnetic field during the sintering of the blank, the oxide material is migrated in the heating element and the oxide material distribution with different thermal conductivity coefficients is formed, which solves the problem that existing heating elements are difficult to accurately control the temperature, and realizes the fine temperature control of the heating element and the adaptation of aerosol products.
Patent Information
- Application Number
- CN202411971923.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
The heating bodies of existing heating cigarettes are difficult to accurately control the temperature, resulting in insufficient or bad taste of aerosols and excessive release of harmful substances.
By applying an external magnetic field during the sintering of the blank, the oxide material is migrated in the heating body, forming oxide materials with different thermal conductivity coefficients distributed in different parts of the heating body, so as to achieve different temperatures and fine temperature control in different areas of the heating body when heating.
It realizes fine temperature control of the heating body and adapts to the heating needs of aerosol products. It can not only ensure the heating effect, but also avoid the adverse experience caused by overall or local overheating, and reduce the release of harmful substances.
Smart Images

Figure CN119638382A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tobacco equipment, and in particular to a heating element and a preparation method thereof. Background Art
[0002] Heated cigarettes are usually used in conjunction with corresponding heated smoking devices, which heat the smoking devices to produce aerosols containing nicotine for consumers to inhale. Compared with the temperature of traditional cigarettes, which is as high as 800°C, the heating temperature of heated cigarettes usually does not exceed 400°C, which significantly reduces the content of harmful components in the aerosol, reduces the impact on consumer health, and reduces pollution to the environment.
[0003] The heating element is the core component of the heated smoking device, which has an important impact on the amount of aerosol produced and the taste quality. However, the heating element currently used has a temperature that is too low, which easily leads to insufficient aerosol production, while a temperature that is too high will produce a bad taste and increase the release of harmful substances, making it difficult to accurately control the temperature. Summary of the invention
[0004] In order to solve the above technical problems, the first purpose of the present invention is to provide a method for preparing a heating element, and the second purpose of the present invention is to provide a heating element obtained by the above preparation method; the preparation method provided by the present application applies an external magnetic field during the sintering process of the green body to make the oxide material migrate in the heating element, so that the oxide materials with different thermal conductivity coefficients are distributed in different parts of the heating element, thereby achieving different temperatures in different areas of the heating element when heating, fine temperature control, and adapting to the heating requirements of aerosol products, which can not only ensure the heating effect, but also avoid the adverse experience caused by overall or local overheating.
[0005] The technical solution provided by the present invention is as follows: A method for preparing a heating element comprises the following steps: S1. Mixing a ceramic phase material, a dispersant, a binder and a solvent to form a slurry; wherein the ceramic phase material comprises at least two oxide materials, wherein at least one oxide material has a higher thermal conductivity than another oxide material; S2. The slurry is made into a green body, and sintered under a protective atmosphere to obtain a heating element; and during the sintering process, an external magnetic field is applied to the green body to make the oxide material migrate in the heating element, so that the distribution of the oxide material in the heating element is different, and the heating temperature is different accordingly.
[0006] Preferably, in parts by weight, the ceramic phase material is 420-460 parts by weight, the dispersant is 5-10 parts by weight, the binder is 10-50 parts by weight, and the solvent is 445-500 parts by weight.
[0007] Preferably, the ceramic phase material is any two or more of aluminum oxide, zirconium oxide, silicon carbide, cubic boron nitride, and hexagonal boron nitride; The dispersant is any one or both of polycarboxylate and polyvinyl pyrrolidone; The binder is one or two of polyvinyl alcohol and polyacrylic acid; The solvent is one or both of water and ethanol.
[0008] Preferably, in the ceramic phase material, the difference in thermal conductivity between the oxide material with the highest thermal conductivity and the oxide material with the lowest thermal conductivity is greater than or equal to 15 W / (m·K).
[0009] Preferably, the ceramic phase material comprises two oxide materials, and the weight ratio of the oxide material with lower thermal conductivity to the oxide material with higher thermal conductivity is 1:(3-19).
[0010] Preferably, in step S1, the ceramic phase material, dispersant, binder and solvent are ball-milled for 6-8 hours at a rotation speed of 400-600 r / min and a ball-to-material ratio of (2-3):1 to prepare a slurry.
[0011] Preferably, in step S2, the sintering is specifically as follows: the heating rate is 3-5°C / min, the sintering temperature is 1600-1700°C, the holding time is 2-4 h, and then the temperature is lowered at a cooling rate of 5-8°C / min; and / or, The protective atmosphere is either nitrogen or helium.
[0012] Preferably, after the furnace temperature reaches the firing temperature, an external magnetic field is applied with a magnetic field strength of 1-5 Tesla and maintained for 1-2 hours.
[0013] Preferably, in step S2, the magnetic lines of force of the external magnetic field are parallel to the axial direction of the heating element.
[0014] A heating element obtained by any of the above-mentioned preparation methods.
[0015] The present application provides a method for preparing a heating element, comprising the following steps: S1, mixing a ceramic phase material, a dispersant, a binder and a solvent to form a slurry; wherein the ceramic phase material includes at least two oxide materials, wherein the thermal conductivity of at least one oxide material is higher than that of another oxide material; S2, making the slurry into a green body, sintering under a protective atmosphere to obtain a heating element; and, during the sintering process, an external magnetic field is applied to the green body to cause the oxide material to migrate in the heating element, so that there is a difference in the distribution of the oxide material in the heating element, and the heating temperature is different accordingly. The preparation method provided by the present application applies an external magnetic field during the green body sintering process to cause the oxide material to migrate in the heating element, so that the oxide materials with different thermal conductivities are distributed in different parts of the heating element, thereby achieving different temperatures in different areas of the heating element when heating, fine temperature control, and adapting to the heating requirements of aerosol products, which can not only ensure the heating effect, but also avoid the adverse experience caused by overall or local overheating.
[0016] Specifically, oxide materials (such as zirconium oxide) are conductive at high temperatures and will be enriched under the action of a magnetic field. Therefore, the external magnetic field applied during the sintering process can affect the arrangement of ceramic particles, causing different oxide materials to selectively aggregate and crystallize at different positions of the heating element, thereby forming regions of different thermal conductivities. This allows the material to achieve a more uniform or gradient distribution of thermal conductivity in the microstructure, thereby optimizing the arrangement and distribution of the material phase composition, and ultimately achieving the preparation of ceramic heating needles with different temperature fields.
[0017] Preferably, among the ceramic phase materials, the difference in thermal conductivity between the oxide material with the highest thermal conductivity and the oxide material with the lowest thermal conductivity is greater than or equal to 15 W / (m·K).
[0018] For example, aluminum oxide and zirconium oxide are selected. Aluminum oxide has a high thermal conductivity of about 18~21.77 W / (m·K), which can effectively transfer heat. The thermal conductivity of zirconium oxide is 2.0~2.5 W / (m·K). In 420-460 parts by weight of ceramic phase materials, 330-418 parts by weight of aluminum oxide and 22-110 parts by weight of zirconium oxide are included, which can ensure that the heating element can generate enough heat and achieve significantly different temperature distributions. In addition, the thermal conductivity of silicon carbide ceramics is 120~200 W / (m·K), the thermal conductivity of cubic boron nitride is 300-500 W / (m·K), and the thermal conductivity of hexagonal boron nitride is 30-200 W / (m·K), and they all have good high temperature resistance, wear resistance, and thermal conductivity, and can also be used.
[0019] Two, three or even more oxide materials can be used, but in order to avoid too many types of oxide materials reacting with each other during the sintering process, or too many types of raw materials generating different phases and affecting the thermal conductivity of the ceramic, it is more preferred to select two of the multiple oxide materials. Among the two oxide materials, the weight ratio of the oxide material with a lower thermal conductivity to the oxide material with a higher thermal conductivity is 1:(3-19), more preferably 1:(4-10).
[0020] When the heating element is used, it is usually inserted into the cigarette in the direction of its axis to heat the smoking material; by making the magnetic lines of force of the external magnetic field parallel to the axis direction of the heating element, the temperature of the heating element close to the end of the cigarette body can be significantly lower than the temperature of the end of the cigarette body, ensuring that the smoking material is effectively heated and avoiding the high temperature of the heating element from having adverse effects on other components of the cigarette. In addition, due to the difference in the temperature of the heating element, the material with high thermal conductivity (such as aluminum oxide) at the end of the heating element inserted into the cigarette has a higher content, which can better release heat and has a higher temperature; the material with low thermal conductivity (such as zirconium oxide) near the end of the cigarette body has a higher content, and the temperature in this area is lower. The temperature at the end of the cigarette inserted close to the tobacco is higher, which can effectively heat the tobacco. The heating element close to the end of the cigarette body will contact other components, and too high a temperature will affect the stable operation of other components. Therefore, the scheme of the present application can effectively avoid overheating, thereby ensuring a softer taste and purer smoke, while reducing the release of harmful substances and avoiding the deterioration of taste.
[0021] More preferably, during the sintering process, the furnace temperature is first increased, and then maintained at a temperature after reaching the firing temperature, and then cooled. The external magnetic field is applied after the temperature reaches the firing temperature, with a magnetic field strength of 1-5 Tesla, and maintained for 1-2 hours. The preferred sintering is specifically as follows: the heating rate is 3-5°C / min, the firing temperature is 1600-1700°C, the holding time is 2-4 hours, and then the temperature is cooled, and the cooling rate is 5-8°C / min.
[0022] In the present application, the ceramic phase material, dispersant, binder and solvent are preferably mixed by ball milling to form a slurry with good fluidity. Specifically, the ceramic phase material, dispersant, binder and solvent are ball milled for 6-8 hours at a speed of 400-600 r / min and a ball-to-material ratio of (2-3):1. Preferably, agate balls are used as grinding balls.
[0023] Among them, polycarboxylate dispersants refer to dispersants with long-chain polymer structures, including polyvinyl alcohol-polyacrylic acid complexes, sodium polyacrylate, polycarboxylate water reducers, and the like.
[0024] In the present application, the process of making the slurry into a green body can adopt a method known in the art. For example, the prepared slurry is poured into the slurry tank of the tape casting machine, and a slurry layer of a certain thickness is formed by control by a scraper. After the coating and drying process is completed, a ceramic heating element is prepared, and an electrode is plated by screen printing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a photograph of the temperature distribution of the heating element in Example 2 of the present invention. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0028] Example 1 A method for preparing a heating element comprises the following steps: S1. Ceramic phase material (Al 2 O 3 Powder 396 parts by weight, ZrO 2 Powder 44 parts by weight, Al 2 O 3 :ZrO 2 =9:1), dispersant (10 parts by weight of polyvinyl pyrrolidone), binder (50 parts by weight of polyvinyl alcohol) and solvent (500 parts by weight of water) were placed in a ball mill at a speed of 500 r / min, in a mass ratio of agate balls to slurry of 2:1, and then loaded into a ball mill, ball milled for 6 hours to make a slurry; S2, pouring the slurry into the slurry tank of the tape casting machine, and controlling it by a scraper to form a slurry layer of a certain thickness, and after completing the coating and drying process, preparing a green body, and plating the electrode by screen printing; the green body is needle-shaped, the length of the green body in the axial direction is 20mm, and the diameter perpendicular to the axial direction is 3mm; The green body was placed in a muffle furnace and sintered under nitrogen protection according to the following conditions: heating rate of 3°C / min, firing temperature of 1600°C, holding time of 2h, then cooling at a cooling rate of 5°C / min; and, after the furnace temperature reached 1600°C, an external magnetic field was applied, the magnetic field lines of the external magnetic field were parallel to the axis direction of the heating element, the magnetic field strength was 1 Tesla, and it was maintained for 2h.
[0029] The test results show that the water absorption rate of the prepared ceramic heating needle is 0.274% and the density is 4.01 g / cm 3 .
[0030] The test results show that the Al 2 O 3 The content of ZrO is 98.24%, 2 The content of Al is 1.76%. 2 O 3 The content is 85.29%, ZrO 2 The content of is 14.71%. After the current is passed, the temperature of the top of the ceramic heating needle can reach 321.49℃, and the temperature of the end close to the smoking device body is 115.67℃.
[0031] Example 2 A method for preparing a heating element comprises the following steps: S1. Ceramic phase material (Al 2 O 3 Powder 352 parts by weight, ZrO 2 Powder 88 parts by weight, Al 2 O 3 :ZrO 2 =8:2), dispersant (10 parts by weight of sodium polyacrylate), binder (50 parts by weight of polyacrylic acid) and solvent (500 parts by weight of ethanol) were placed in a ball mill at a speed of 600 r / min, in a mass ratio of agate balls to slurry of 3:1, and then loaded into a ball mill, and ball milled for 5 hours to make a slurry; S2, pouring the slurry into the slurry tank of the tape casting machine, and controlling it by a scraper to form a slurry layer of a certain thickness, and after completing the coating and drying process, preparing a green body, and plating the electrode by screen printing; the green body is needle-shaped, the length of the green body in the axial direction is 20mm, and the diameter perpendicular to the axial direction is 3mm; The green body was placed in a muffle furnace and sintered under nitrogen protection according to the following conditions: heating rate of 3°C / min, firing temperature of 1600°C, holding time of 2h, then cooling at a cooling rate of 5°C / min; and, after the furnace temperature reached 1600°C, an external magnetic field was applied, the magnetic field lines of the external magnetic field were parallel to the axis direction of the heating element, the magnetic field strength was 1 Tesla, and it was maintained for 2h.
[0032] The test results show that the water absorption rate of the prepared ceramic heating needle is 0.368% and the density is 4.26 g / cm 3 .
[0033] The test results show that the Al 2 O 3 The content of ZrO is 97.20%, 2 The content of Al is 2.80%. 2 O 3 The content is 78.54%, ZrO 2 The content of is 21.46%. After the current is passed, the temperature of the top of the ceramic heating needle can reach 323.66℃, and the temperature of the end close to the smoking device body is 79.51℃.
[0034] Example 3 A method for preparing a heating element comprises the following steps: S1. Ceramic phase material (Al 2 O 3 Powder 396 parts by weight, ZrO 2 Powder 44 parts by weight, Al 2 O 3 :ZrO 2 =9:1), dispersant (polyvinyl pyrrolidone 10 parts by weight), binder (polyacrylic acid 50 parts by weight) and solvent (ethanol 500 parts by weight) were placed in a ball mill at a speed of 450 r / min, in a ratio of agate balls to slurry of 2:1, and then loaded into a ball mill, ball milled for 8 hours to make a slurry; S2, pouring the slurry into the slurry tank of the tape casting machine, and controlling it by a scraper to form a slurry layer of a certain thickness, and after completing the coating and drying process, preparing a green body, and plating the electrode by screen printing; the green body is needle-shaped, the length of the green body in the axial direction is 20mm, and the diameter perpendicular to the axial direction is 3mm; The green body was placed in a muffle furnace and sintered under nitrogen protection according to the following conditions: heating rate of 3°C / min, firing temperature of 1600°C, holding time of 2h, then cooling at a cooling rate of 5°C / min; and, after the furnace temperature reached 1600°C, an external magnetic field was applied, the magnetic field lines of the external magnetic field were parallel to the axis direction of the heating element, the magnetic field intensity was 1 Tesla, and it was maintained for 1h.
[0035] The test results show that the water absorption rate of the prepared ceramic heating needle is 0.261% and the density is 4.02 g / cm 3 .
[0036] The test results show that the Al2 O 3 The content of ZrO is 98.04%, 2 The content of Al is 1.96%. 2 O 3 The content is 88.08%, ZrO 2 The content of is 11.92%. After the current is passed, the temperature of the top of the ceramic heating needle can reach 317.26℃, and the temperature of the end close to the smoking device body is 119.82℃.
[0037] Example 4 A method for preparing a heating element comprises the following steps: S1. Ceramic phase material (Al 2 O 3 Powder 396 parts by weight, ZrO 2 Powder 44 parts by weight, Al 2 O 3 :ZrO 2 =9:1), dispersant (10 parts by weight of polyvinyl pyrrolidone), binder (50 parts by weight of polyacrylic acid) and solvent (500 parts by weight of ethanol) were placed in a ball mill at a speed of 500 r / min, in a mass ratio of agate balls to slurry of 2:1, and then loaded into a ball mill, ball milled for 6 hours to make a slurry; S2, pouring the slurry into the slurry tank of the tape casting machine, and controlling it by a scraper to form a slurry layer of a certain thickness, and after completing the coating and drying process, preparing a green body, and plating the electrode by screen printing; the green body is needle-shaped, the length of the green body in the axial direction is 20mm, and the diameter perpendicular to the axial direction is 3mm; The green body was placed in a muffle furnace and sintered under nitrogen protection according to the following conditions: heating rate of 3°C / min, firing temperature of 1600°C, holding time of 2h, then cooling at a cooling rate of 5°C / min; and, after the furnace temperature reached 1600°C, an external magnetic field was applied, the magnetic field lines of the external magnetic field were parallel to the axis direction of the heating element, the magnetic field strength was 3 Tesla, and it was maintained for 2h.
[0038] The test results show that the water absorption rate of the prepared ceramic heating needle is 0.261% and the density is 4.02 g / cm 3 .
[0039] The test results show that the Al 2 O 3 The content of ZrO is 99.17%, 2 The content of Al is 0.83%. 2 O 3 The content is 83.64%, ZrO 2The content of is 16.36%. After the current is passed, the temperature of the top of the ceramic heating needle can reach 328.48℃, and the temperature of the end close to the smoking device body is 109.68℃.
[0040] Comparative Example 1 A method for preparing a heating element comprises the following steps: S1. Ceramic phase material (Al 2 O 3 Powder 396 parts by weight, ZrO 2 Powder 44 parts by weight, Al 2 O 3 :ZrO 2 =9:1), dispersant (10 parts by weight of polyvinyl pyrrolidone), binder (50 parts by weight of polyvinyl alcohol) and solvent (500 parts by weight of water) were placed in a ball mill at a speed of 500 r / min, in a mass ratio of agate balls to slurry of 2:1, and then loaded into a ball mill, ball milled for 6 hours to make a slurry; S2, pouring the slurry into the slurry tank of the tape casting machine, and controlling it by a scraper to form a slurry layer of a certain thickness, and after completing the coating and drying process, preparing a green body, and plating the electrode by screen printing; the green body is needle-shaped, the length of the green body in the axial direction is 20mm, and the diameter perpendicular to the axial direction is 3mm; The green body was placed in a muffle furnace and sintered under nitrogen protection according to the following conditions: heating rate of 3°C / min, firing temperature of 1600°C, holding time of 2h, then cooling at a cooling rate of 5°C / min; no external magnetic field was applied during the sintering process.
[0041] The test results show that the water absorption rate of the prepared ceramic heating needle is 0.261% and the density is 4.02 g / cm 3 .
[0042] The test results show that the Al 2 O 3 The content of ZrO is 89.76%, 2 The content of Al is 10.24%. 2 O 3 The content is 90.08%, ZrO 2 The content of is 9.92%. After the current is passed, the temperature of the top of the ceramic heating needle can reach 258.14℃, and the temperature of the end close to the smoking device body is 251.03℃.
[0043] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a heating element, characterized in that: The following steps are involved: S1. Mixing a ceramic phase material, a dispersant, a binder and a solvent to form a slurry; wherein the ceramic phase material comprises at least two oxide materials, wherein at least one oxide material has a higher thermal conductivity than another oxide material; S2, making the slurry into a green body, and sintering it under a protective atmosphere to obtain a heating element; Furthermore, during the sintering process, an external magnetic field is applied to the green body to cause the oxide material to migrate in the heating element, so that the distribution of the oxide material in the heating element is different, and the heating temperature is also different accordingly.
2. The preparation method according to claim 1, characterized in that: In parts by weight, the ceramic phase material is 420-460 parts by weight, the dispersant is 5-10 parts by weight, the binder is 10-50 parts by weight, and the solvent is 445-500 parts by weight.
3. The preparation method according to claim 1, characterized in that: The ceramic phase material is any two or more of alumina, zirconium oxide, silicon carbide, cubic boron nitride, and hexagonal boron nitride; The dispersant is any one or both of polycarboxylate and polyvinyl pyrrolidone; The binder is one or two of polyvinyl alcohol and polyacrylic acid; The solvent is one or both of water and ethanol.
4. The preparation method according to any one of claims 1 to 3, characterized in that Among ceramic phase materials, the difference in thermal conductivity between the oxide material with the highest thermal conductivity and the oxide material with the lowest thermal conductivity is greater than or equal to 15 W / (m·K).
5. The preparation method according to claim 4, characterized in that: The ceramic phase material includes two oxide materials, and the weight ratio of the oxide material with lower thermal conductivity to the oxide material with higher thermal conductivity is 1:(3-19).
6. The preparation method according to claim 1, characterized in that: In step S1, the ceramic phase material, dispersant, binder and solvent are ball-milled for 6-8 hours at a rotation speed of 400-600 r / min and a ball-to-material ratio of (2-3):1 to prepare a slurry.
7. The preparation method according to claim 1, characterized in that: In step S2, the sintering is specifically as follows: the heating rate is 3-5°C / min, the sintering temperature is 1600-1700°C, the holding time is 2-4 hours, and then the temperature is lowered at a cooling rate of 5-8°C / min; and / or, The protective atmosphere is either nitrogen or helium.
8. The preparation method according to claim 7, characterized in that: After the furnace temperature reaches the firing temperature, an external magnetic field is applied with a magnetic field strength of 1-5 Tesla and maintained for 1-2 hours.
9. The preparation method according to any one of claims 1-3 and 5-8, characterized in that: In step S2, the magnetic lines of force of the external magnetic field are parallel to the axial direction of the heating element.
10. The heating element obtained by the preparation method according to any one of claims 1 to 9.